The effects of transcranial direct current stimulation on attention and inhibitory control of children and adolescents with attention-deficit/hyperactivity disorder (ADHD): Study protocol for a randomized, sham-controlled, triple-blind, cross-over trial. Issue 8 (26th February 2021) - Guimarães, Rachel Silvany Quadros; Bandeira, Igor D.; Barretto, Bianca Lima; Barretto, Thiago Lima; Wanke, Thamires; Alves, Clara Oliveira Carvalho; de Carvalho, Chrissie Ferreira; Lucena, Pedro H.; Rodrigues-Silva, Luciana; Lucena, Rita
Abstract : Abstract: Attention-deficit/hyperactivity disorder (ADHD) is characterized by a persistent pattern of inattention and hyperactivity/impulsivity. Despite the proven efficacy of pharmacological treatment, many individuals continue to suffer socially and academically and some experience significant side effects that negate the use psychotropic drugs. Transcranial direct current stimulation (tDCS) is a cortical neuromodulation feature that has shown positive results in the treatment of various neuropsychiatric conditions. Objectives: To investigate the effect of tDCS on the performance of children and adolescents with ADHD in the neuropsychological tests of visual attention, verbal, and inhibitory control. Methodology: Triple blind, randomized, sham-controlled, cross-over trial involving tDCS in children and adolescents with ADHD. Initial screening will be performed using Swanson, Nolan, and Pelham – IVand Wechsler intelligence scale for children fourth edition vocabulary and cube subtests. Individuals will be evaluated pre-tDCS and post-tDCS with the Wechsler intelligence scale for children fourth edition Digitus subtest, neuropsychological assessment battery second edition inhibiting responses subtest, Corsi cubes, and visual attention test-4.